2019
DOI: 10.1021/acsami.9b00389
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing High-Voltage Performance of Ni-Rich Cathode by Surface Modification of Self-Assembled NASICON Fast Ionic Conductor LiZr2(PO4)3

Abstract: Coating methodology is commonly employed in the enhancement of Ni-rich cathodes for Li-ion batteries as an efficient approach, while its strategy and effect are still great challenges to achieve success in surface modifications for comprehensive electrochemical properties. In this work, the surface of Ni-rich cathode LiNi0.82Co0.15Al0.03O2 (NCA) is modified by intimately coating NASICON-type solid electrolyte LiZr2(PO4)3 (LZP) via a facile approach involving electrostatic attraction. With well-designed archite… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
55
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 131 publications
(58 citation statements)
references
References 62 publications
3
55
0
Order By: Relevance
“…[34] Moreover,t he percentage of absorbed oxygen (89.76 %) after coating is lower than that of the pristine material( 91.30 %), determined by using Avantage software. It is provedt hat the contento fr esidual lithium salt is reduced: Li 4 P 2 O 7 [16] and LiZr 2 (PO 4 ) 3 [18] could be generatedd uring the process of ZrP 2 O 7 formation. The bond dissociation energies (DH f298 ,k J À1 mol À1 )o fe ach atom with Oa toms were reported to be CoÀO( 368.0), NiÀO( 391.6), MnÀO( 402), PÀO( 596.6), ZrÀO( 760.0), [35] and strong covalent bonds can increase the chemicals tabilityo ft he coating material andi nhibit the attack of HF in the electrolyte, whicht hen improves the electrochemical performance of the NCM811.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…[34] Moreover,t he percentage of absorbed oxygen (89.76 %) after coating is lower than that of the pristine material( 91.30 %), determined by using Avantage software. It is provedt hat the contento fr esidual lithium salt is reduced: Li 4 P 2 O 7 [16] and LiZr 2 (PO 4 ) 3 [18] could be generatedd uring the process of ZrP 2 O 7 formation. The bond dissociation energies (DH f298 ,k J À1 mol À1 )o fe ach atom with Oa toms were reported to be CoÀO( 368.0), NiÀO( 391.6), MnÀO( 402), PÀO( 596.6), ZrÀO( 760.0), [35] and strong covalent bonds can increase the chemicals tabilityo ft he coating material andi nhibit the attack of HF in the electrolyte, whicht hen improves the electrochemical performance of the NCM811.…”
Section: Resultsmentioning
confidence: 99%
“…[11] Single layer or multilayer coatings are formed on the surface of the material, whichc an transfer electrons or ions and protect the cathode from electrolyte corrosion. [12] Metal oxides or other polyanion materials such as Al 2 O 3 , [13] LaPO 4 , [14] TiP 2 O 7 , [15] Li 4 P 2 O 7 , [16] Li 3 PO 4 /PPy, [17] LiZr 2 (PO 4 ) 3 , [18] Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 , [19,20] Al 2 O 3 /LiAlO 2 , [21] and MoS 2 [22] have been reported to be very effective coating materials. Li et al [23] reported Zr modificationh ad dual functions, one is that Zr 4 + can enter into the lattice of the transition metal plane or lithium plane, the other is that the remaining Zr 4 + floats on the surface of particles, formed aL i 2 ZrO 3 coating layer.…”
Section: Introductionmentioning
confidence: 99%
“…Now that the parasitic side reactions start from the interfaces between the solid cathodes and liquid electrolytes, the most effective method is to avoid their direct contact by introducing passive physical protection layer on the cathode surface . In general, the employed coating species can be categorized into i) the chemically and electrochemically inactive coatings, including metal oxides (Al 2 O 3 , TiO 2 , MgO, SiO 2 , ZrO 2 , V 2 O 5 , Nb 2 O 5 , ZnO, MoO 3 , and Y 2 O 3 ,) and phosphates (AlPO 4 , MnPO 4 , Mn 3 (PO 4 ) 2 , La(PO 4 ) 3 , Ni 3 (PO 4 ) 2 , Co 3 (PO 4 ) 2 , ZrP 2 O 7 , and FePO 4 ) as well as some fluorides (AlF 3 and LiF); ii) the Li + conductive coatings, mainly refer to the Li‐containing compounds such as LiAlO 2 , Li 2 ZrO 3 , Li 3 VO 4 , Li 2 MnO 3 , LiMn 2 O 4 , Li 3 PO 4 (LPO), LiFePO 4 (LFP), LiMnPO 4 , Li 2 TiO 3 , LiTiO 2 , Li 2 O‐2B 2 O 3 , LiTi 2 (PO 4 ) 3 , LiZr 2 (PO 4 ) 3 , Li 1.4 Al 0.4 Ti 1.6 (PO 4 ) 3 , Li 0.5 La 0.5 TiO 3 , LiTaO 3 , Li 4 SiO 4 , and LiAlF 4 as well as some heterostructured electrochemical active cathodes (Li 1.2 Ni 0.2 Mn 0.6 O 2 , Li 1.2 Mn 0.54 Ni 0.13 Co 0.13 O 2 and NCM333); and iii) the electron conducting coating, representatively, reduced graphene oxide (rGO), permeable poly (3,4‐ethylenedioxythiophene) (PEDOT),…”
Section: Strategies To Mitigate the Surface/interface Structure Degramentioning
confidence: 99%
“…Residual lithium compounds (see section 4) have an adverse effect on the electrochemical performance because of their intrinsically low ionic conductivity and subsequent decomposition accompanied by gassing. Some coatings can convert these residuals into reasonably conductive lithium compounds, such as phosphates, and garnets, thereby improving the rate capability. It has been claimed that polymeric coatings, which generally achieve full surface coverage more readily, can prevent cracking by giving elastic support to the secondary particles , .…”
Section: Coatingsmentioning
confidence: 99%